UCH-L1 and UCH-L3 regulate the cancer stem cell-like properties through PI3 K/Akt signaling pathway in prostate cancer cells. Issue 5 (3rd September 2021) - Lee, Jae Eun; Lim, Yun Hwan; Kim, Jung Hwa
ABSTRACT : Castration-resistant prostate cancer (CRPC) is a highly aggressive and advanced prostate cancer that is currently incurable with conventional therapies. The recurrence and chemotherapy-resistant properties of CRPC are attributed to prostate cancer stem cells (CSCs). On the other hand, the factors regulating the prostate CSC-like properties have not been studied extensively. Previously, ubiquitin C-terminal hydrolase-L1 (UCH-L1) and ubiquitin C-terminal hydrolase-L3 (UCH-L3) were reported to be involved in prostate cancer cell progression through the epithelial-to-mesenchymal transition (EMT) regulation. Here, the differential regulation on the CSC-like properties by UCH-L1 and UCH-L3 were identified in prostate cancer cells. The CSC-like characteristics, such as the expression of pluripotency markers, chemoresistance, and sphere-forming ability, were promoted by UCH-L1, whereas those were repressed by UCH-L3. Moreover, the modulation of CSC-like properties by UCH-L1 and UCH-L3 was through the PI3 K/Akt signaling pathway. The CSC-like properties induced by UCH-L1 overexpression or UCH-L3 depletion were suppressed by the PI3 K/Akt pathway inhibitor. In conclusion, UCH-L1 and UCH-L3 are novel regulators of the CSC-like properties and shed light on new therapeutic strategies to overcome CSCs in prostate cancers.